Addition of silicon to boron foliar spray in cotton plants modulates the antioxidative system attenuating boron deficiency and toxicity - de Souza Júnior, Jonas P. [UNESP]; de M Prado, Renato [UNESP]; Campos, Cid N. S.; Sousa Junior, Gilmar S. [UNESP]; Oliveira, Kevein R.; Cazetta, Jairo O. [UNESP]; Gratão, Priscila L. [UNESP] (Springer Nature, 2022)
Background: Boron (B) nutritional disorders, either deficiency or toxicity, may lead to an increase in reactive oxygen species production, causing damage to cells. Oxidative damage in leaves can be attenuated by supplying silicon (Si). The aim of this study was to assess the effect of increasing foliar B accumulation on cotton plants to determine whether adding Si to the spray solution promotes gains to correct deficiency and toxicity of this micronutrient by decreasing oxidative stress via synthetizing proline and glycine-betaine, thereby raising dry matter production. Results: B deficiency or toxicity increased H2O2 and MDA leaf concentration in cotton plants. H2O2 and MDA leaf concentration declined, with quadratic adjustment, as a function of increased leaf B accumulation. Proline and glycine-betaine leaf concentration increased under B-deficiency and B-toxicity. In addition, production of these nonenzymatic antioxidant compounds was greater in plants under toxicity, in relation to deficient plants. Adding Si to the B spray solution reduced H2O2 and MDA concentration in the plants under nutrient deficiency or toxicity. Si reduced H2O2, primarily in B-deficient plants. Si also increased proline and glycine-betaine concentration, mainly in plants under B toxicity. Dry matter production of B-deficient cotton plants increased up to an application of 1.2 g L− 1 of B. The critical B level in the spray solution for deficiency and toxicity was observed at a concentration of 0.5 and 1.9 g L− 1 of B, respectively, in the presence of Si, and 0.4 and 1.9 g L− 1 of B without it. In addition, the presence of Si in the B solution raised dry matter production in all B concentrations evaluated in this study. Conclusion: Our findings demonstrated that adding Si to a B solution is important in the foliar spraying of cotton plants because it increases proline and glycine-betaine production and reduces H2O2 and MDA concentration, in addition to mitigating the oxidative stress in cotton plants under B deficiency or toxicity.
Keywords: Beneficial element; Gossypium hirsutum (cotton); Leaf spray; Non-enzymatic antioxidative mechanisms; Nutritional disorder